The influence of strategic patenting on companies' patent portfolios - Knut Blind; Katrin Cremers; Elisabeth Mueller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper analyses whether strategic motives for patenting influence the characteristics of companies' patent portfolios. We use the number of citations and oppositions to represent these characteristics. The investigation is based on survey and patent data from German companies. We find clear evidence that the companies' patenting strategies explain the characteristics of their patent portfolios. First, companies using patents to protect their technological knowledge base receive a higher number of citations for their patents. Second, the motive of offensive - but not of defensive - blocking is related to a higher incidence of oppositions, whereas companies using patents as bartering chips in collaborations receive fewer oppositions to their patents.
Older version: http://hdl.handle.net/10419/24565
Keywords: O34; O32; 330; strategic patenting; patent portfolio characteristics; Patent; Wettbewerbsstrategie; Portfolio-Management; Wettbewerbsbeschränkung; Publikationsanalyse; Schätzung; Deutschland